Judges 1 : A Commentary on Judges 1:1 - 10:5 - Smith, Mark S. (Book collections on Project MUSE., 2021)
This groundbreaking volume presents a new translation and detailed interpretation of the book of Judges, drawing on archaeology and iconography, textual versions, biblical parallels, and extrabiblical texts, as well as a thorough review of modern scholarship. Full literary and redactional analyses are included. Notably, archaeology is used to show how a story of the Iron II period employed visible ruins to narrate supposedly early events from the so-called ""period of the Judges.""